erception of Interethnic Relations Through the Prism of Security of the Republic of Serbia - Radončić, Hajradin M.; Karović, Samed M.; Jeftić, Zoran S. (Sociološki pregled, 2019)
The paper analyzes interethnic relations in the Republic of Serbia that may have an impact on the security of the Republic of Serbia. The purpose of this paper is to examine and explain the elements relevant to the security system from the perspective of interethnic relations through the attitudes of members of churches and religious communities. The research was conducted through survey testing and directed orientation interviews with representatives of the Islamic community in the Republic of Serbia, in places where the inhabitants of this community live, the representatives of state administration, local and regional authorities.